2001
DOI: 10.2135/cropsci2001.412335x
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Correlated Responses to Divergent Selection for Leaf Abscisic Acid Concentration in Two Maize Populations

Abstract: Abscisic acid (ABA) concentration can affect plant responses to drought and has been suggested as a selection criterion to improve drought tolerance. Divergent selection for high (H) and low (L) leaf ABA concentration was conducted under moderate drought conditions in the F2 of maize (Zea mays L.) single crosses Os420 × IABO78 and Mo17 × B88. Objectives of this study were to evaluate direct and correlated responses to the divergent selection. For each cross, the F2 and the H‐ and L‐populations (H‐P and L‐P) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 33 publications
0
14
0
Order By: Relevance
“…The extent and rate of ABA accumulation varies with species or cultivars differing in drought tolerance (Conti et al, 1994;Pekic et al, 1995). Previous studies with annual crops have demonstrated a relationship between low ABA accumulation and drought tolerance (Durley et al, 1983;Innes et al, 1984;Landi et al, 2001). A drought-tolerant cultivar of orchardgrass exhibited lower leaf ABA accumulation compared with a droughtsusceptible cultivar (Volaire et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The extent and rate of ABA accumulation varies with species or cultivars differing in drought tolerance (Conti et al, 1994;Pekic et al, 1995). Previous studies with annual crops have demonstrated a relationship between low ABA accumulation and drought tolerance (Durley et al, 1983;Innes et al, 1984;Landi et al, 2001). A drought-tolerant cultivar of orchardgrass exhibited lower leaf ABA accumulation compared with a droughtsusceptible cultivar (Volaire et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…3), which may be attributed to the role of ABA in suppressing the increases in electrolyte leakage (Rajasekaran &Blake, 1999 andSewelam et al, 2017), suggesting that ABA could reduce drought injury by protecting cell membranes and photosynthetic apparatus. The reported synthesis of dehydrin proteins under ABA treatment may represent another protective process induced by ABA (Landi et al, 2001).…”
Section: Camentioning
confidence: 94%
“…Selective pressure for yield increases may have eliminated genotypes with higher sensitivity to, or higher concentrations of ABA. In C 4 maize, Landi et al (2001) demonstrated that selection for low ABA leaf concentration generated genetic lines with higher yield performance in most agronomic conditions, including water-limiting conditions. In spring wheat, lines selected for low ABA concentration performed better under both irrigated and drought stress conditions for total biomass and grain yield (Read et al, 1991).…”
Section: Hypothesis Four: Breeders Inadvertently Selected Formentioning
confidence: 99%